E a trajet??ria de vida se alonga al??m dos 60 anos... o idoso universit??rio - Carraro, Val??ria (2016)
The advancing age of the population has mobilized continuous developments and discoveries in many areas and fields of knowledge to maintain or increase the capacity for autonomy, participation, enjoyment, livelihoods and preserving the quality of life for seniors, people aged 60 years or more. In this context, this study investigates six university elderly people who were enrolled in an undergraduate degree in a regular classroom and educational institution, attend classes, perform academic activities and live together in an intergenerational environment. This work was based on the qualitative research methodology. Oral reports of elderly people were heard, three men and three women. After the content analysis of the recorded and transcribed interviews, five recurring themes were identified that made it possible to answer questions relating to the individual's motivation to join a regular degree course, the intergenerational experiences and future expectations after completion of the course; in addition to expanding the information about human aging. The theoretical framework is anchored in Complex Thought proposed by Edgar Morin, in the subject and subjectivity notions and operators that articulate the Complexity Theory, the dialogic, recursive and holographic principles. It was concluded that for the elderly respondents, even with numerous challenges due to age, the benefits of learning are clear and satisfactory as nurture intergenerational relationships, acquisition of new knowledge and the ability to glimpse a new beginning of a new career and become new social actors. Education has a democratic role and is a social and human right, regardless of age. Think of education for the elderly is the same as thinking in improving their quality of life and the possibilities of transformation in the social, cultural and intellectual of the subject. All acquired knowledge can interfere and change the relationship to the extent that this legitimizes the authority and the conquest of citizenship.